THE RISE OF LUKARAWA: ANALYZING THE FACTORS CONTRIBUTING TO THE EMERGENCE OF A NEW TERRORIST GROUP IN NIGERIA - Ogele, Eziho Promise (Journal of Terrorism Studies, 2025)
The paper examined historical and socio-economic factors contributing to the emergence of Lakurawa terrorism in North West Nigeria. The Lakurawa is one of the terrorist organizations operated in Nigerian Republic's forests that is situated along its shoreline, which became a haven for terrorist groups. Approximately seven camps are operating in areas such as Bangi, Dankano, Galmi, Maradi, Masallata, and YarBasira. The strategic location enables free movement between Nigeria and Niger, facilitating the establishment of hidden camps within the vast bushlands of the region. The absence of the federal government created an ungoverned space, leading to a power vacuum. The paper was elicited through a secondary data gathering technique. The paper revealed that Lukarawara emerged in the northwest of Nigeria via the invitation of the residents to support in the fight against armed bandits. However, the relationship quickly deteriorated due to accusations of cattle theft and attempts to enforce strict Islamic law. The success of Lukarawa's attacks is a combination of factors, including cultural affinity, religious affiliation, porous border, bad governance, economic inequality, and high poverty rates. The paper recommends, amongst others, that the Nigerian government should prioritise rebuilding its partnership with the Nigerien junta to revitalise their mutually beneficial military alliance.